Is endothelial dysfunction the one to blame in heart failure with preserved ejection fraction? - Ferreira, Carla Sofia Gomes (2015)
Dissertação de mestrado em Investigação Biomédica, apresentada á Faculdade de Medicina da Universidade de Coimbra